2001
DOI: 10.1007/s004210100459
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the BOD POD for estimating percentage body fat in a heterogeneous group of adult humans

Abstract: The primary purpose of this investigation was to compare estimations of percentage body fat (%fat) using air displacement plethysmography (ADP) and hydrostatic weighing (HW) in a heterogeneous (age and %fat) sample of the population. Of secondary importance was to determine whether there were differences between the two methods among lean (n = 32), average (n = 34) and overweight (n = 29) subsets of this sample. A total of 95 adults (men 27, women 68) ranging in age from 18-52 years volunteered for this study.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
60
1
3

Year Published

2003
2003
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(67 citation statements)
references
References 12 publications
3
60
1
3
Order By: Relevance
“…Nevertheless, ADP may still be a more practical and equally precise method of body composition measurement in children compared with HW, especially in multi-compartment models (Wells & Fuller, 2001). The test-retest variability in measured raw body volume, equivalent to 0.8% BF was less than (Demerath et al, 2002) or comparable with that found in some studies (Miyatake et al, 1999;Vescovi et al, 2001;Wells & Fuller, 2001), but greater than that found by others (McCrory et al, 1995;Collins et al, 1999). However, unlike some of these studies, the variation in measured body volume was assessed in repeats of the whole test procedure (which consisted of the mean of two serial measures of raw volume), and so better highlighted precision of one complete procedure.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Nevertheless, ADP may still be a more practical and equally precise method of body composition measurement in children compared with HW, especially in multi-compartment models (Wells & Fuller, 2001). The test-retest variability in measured raw body volume, equivalent to 0.8% BF was less than (Demerath et al, 2002) or comparable with that found in some studies (Miyatake et al, 1999;Vescovi et al, 2001;Wells & Fuller, 2001), but greater than that found by others (McCrory et al, 1995;Collins et al, 1999). However, unlike some of these studies, the variation in measured body volume was assessed in repeats of the whole test procedure (which consisted of the mean of two serial measures of raw volume), and so better highlighted precision of one complete procedure.…”
Section: Discussionsupporting
confidence: 61%
“…The BODPOD takes a correction for the negative volume effect of isothermal air close to the skin by use of a derived surface area artifact (SAA), highly dependent on estimated body surface area as described below. As body surface area estimation is a main determinant of this SAA it may be a possible source of inaccuracy within this method (Vescovi et al, 2001). …”
Section: Discussionmentioning
confidence: 99%
“…4,6,11,18,19,25 These values are also probably dependent to some extent on prevailing ambient conditions and variations in the performance of individual instruments, although the latter should be minimized as each instrument is of a standard manufactured by a single company. Accordingly, a variable level of precision (although even the worst case was still very good) has been observed in a number of different subjects undergoing repeated measurements in other studies ( JCK Wells and JE Williams, unpublished).…”
Section: Discussionmentioning
confidence: 99%
“…The reported correlation between the Bod Pod and hydrostatic weighing was r = 0.88. 14) All subjects were interviewed by experienced dietitians using a food frequency questionnaire (FFQ), which is based on 29 food groups and 10 types of cooking, for estimating the energy and nutrient intakes of each subject during the past 1-2 months. 15) From the FFQ, the mean daily energy intake was calculated according to the Tables of Japanese Foodstuff Composition.…”
Section: Methodsmentioning
confidence: 99%